Efficient CO2/N2 and CO2/CH4 separation using NH2-MIL-53(Al)/cellulose acetate (CA) mixed matrix membranes - Mubashir, M. (Elsevier B.V., 2018)
In the current study, new types of MMMs are fabricated by incorporating NH2-MIL-53(Al) filler into cellulose acetate (CA) polymer. Subsequently, crystallinity, morphology, thermal stability, functional groups and density measurement of the resultant MMMs were verified by using different analytical tools. The results showed that the presence of NH2-MIL-53(Al) in CA matrix had enhanced the CO2 permeability, CO2/N2 and CO2/CH4 ideal selectivities from 15.5 Barrer to 52.6 Barrer, 8.8 to 23.4 and 10.7 to 28.7, respectively. The present study revealed that the addition of 15 wt NH2-MIL-53(Al) MOF into the CA matrix resulted in highest enhancement of FFV. Furthermore, MMM loaded with 15 wt NH2-MIL-53(Al) demonstrated highest CO2 permeability as well as CO2/CH4 and CO2/N2 selectivities of 52.6 Barrer, 28.7 and 23.4, respectively. Besides, the resultant MMM showed CO2 plasticization resistance of up to 30 bar, which is 200 increment in comparison of pristine CA membrane which is only 10 bar. This work also revealed that the resultant MMMs showed significantly higher CO2 separation performance compared to the results previously reported for CA-based MMMs. Thus, it can be concluded that the MMMs fabricated in the present work has potential for CO2 removal from the flue gas and natural gas at industrial scale. Â© 2018 Elsevier B.V.